Development of Optical Bone Densitometry Using Near-infrared Light / Kaname Miura ...[et al.] - Kaname, Miura; Hidenori, Matsubara; Shigeo M., Tanaka (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In order to realize the early detection of osteoporosis, development of a device that enables simple screening is desirable. We have focused on a simple bone density evaluation method using near-infrared light and have studied its reliability. In this study, we propose an optical bone density measurement method, in which bone density is evaluated by the slope of light intensity on the skin surface. A detection system of quasi-ballistic light is incorporated into this method for better accuracy, by decreasing the influence of light scattering in the skin layer. This method was verified by Monte Carlo simulation and experiments using bone and skin phantoms. In the simulation, we made an analytical model, based on the proposed method, to investigate the propagation behavior of photons in skin and bone tissues, and the light intensity distribution on the surface of the skin was analyzed. In the experiment, a computer-controlled apparatus was developed, based on the proposed method, for the detection of light intensity distribution on the surface of the skin phantom and calcined bovine cancellous bone, respectively. The skin surface was irradiated with near-infrared laser light (wavelength: 850 nm) and the light intensity was measured over the surface using the apparatus. A positive correlation was obtained for the relationship between the slope of the light intensity distribution and the bone density, within the range of 2 mm or less of skin thickness. This experimental result was qualitatively supported by the simulation results. In particular, the correlation in the range of 1 to 1.5 mm of skin thickness suggested an acceptable accuracy for this method.